Faktor-Faktor Yang Mempengaruhi Efektivitas Sistem Informasi Akuntansi Pada Opd Kabupaten Aceh Tamiang - Indah Putri; Afrah Junita; Mayang Murni (Transformasi: Journal of Economics and Business Management, 2024)
The effectiveness of Accounting Information Systems is an indicator that measures the extent to which the target achievement of transforming data into information to support decision-making in government institutions. This research aims to investigate the impact of work experience, accounting understanding, and technological sophistication on the effectiveness of Accounting Information Systems. It was conducted using quantitative research methods with primary data from 72 respondents through questionnaires distributed to 24 OPDs in Aceh Tamiang District. Sampling was done using purposive sampling techniques. Data analysis was performed using multiple linear regression with IBM SPSS 25 application. The research findings indicate that work experience and accounting understanding significantly influence the effectiveness of Accounting Information Systems, while technological sophistication does not have a significant influence. However, collectively, these three factors have a significant impact on the effectiveness of Accounting Information Systems.